2020
DOI: 10.3390/catal10050485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduction Atmosphere on Structure and Catalytic Performance of PtIn/Mg(Al)O/ZnO for Propane Dehydrogenation

Abstract: The effect of reduction atmospheres, H2/N2, C3H8/H2/N2, C3H8 and CO, on the structure and propane direct dehydrogenation performance of PtIn/Mg(Al)O/ZnO catalyst derived from ZnO-supported PtIn-hydrotalcite was studied. The physicochemical properties of the as-prepared and used catalytic system were characterized by various characterization methods. The results show that the dehydrogenation performance, especially the stability of the PtIn/Mg(Al)O/ZnO catalyst, was significantly improved along with the change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Currently, adding metal promoters to form alloys or intermetallic compounds is one of the most effective methods to ameliorate central active components and inhibit catalytic deactivation in Pt-based catalytic systems. As is generally acknowledged, these promoters are believed to exert geometric and electronic effects pivotally to active components. Metal promoters can inhibit the aggregation of active sites and reduce the number of neighboring Pt atoms within the assembles, and the electron transfer they provide can tune the electronic properties of central sites, increasing the energy barriers of deep dehydrogenation and adjusting the ability to adsorb propylene.…”
Section: Strategies For Catalytic Stability Enhancementmentioning
confidence: 99%
“…Currently, adding metal promoters to form alloys or intermetallic compounds is one of the most effective methods to ameliorate central active components and inhibit catalytic deactivation in Pt-based catalytic systems. As is generally acknowledged, these promoters are believed to exert geometric and electronic effects pivotally to active components. Metal promoters can inhibit the aggregation of active sites and reduce the number of neighboring Pt atoms within the assembles, and the electron transfer they provide can tune the electronic properties of central sites, increasing the energy barriers of deep dehydrogenation and adjusting the ability to adsorb propylene.…”
Section: Strategies For Catalytic Stability Enhancementmentioning
confidence: 99%
“…Some researchers have studied the preparation conditions of magnesium aluminum oxide support, such as Mg/Al molar ratio, pH value, and calcination temperature of the precursor. 83,84 Zhang et al 85 found that the formation of highly crystalline meixnerite can redisperse the metal active sites and adjust the acid-base properties of the catalyst, improving stability and coke resistance.…”
Section: Alumina Supportmentioning
confidence: 99%
“…Now, the focus has been switched to calcined hydrotalcite or hydrotalcitelike (HT) composites, which have been used in direct dehydrogenation of propane and have good performance compared to other supports [10][11][12]. Calcined hydrotalcite or hydrotalcite-like (HT) materials are the typical composite metal oxides [35][36][37]. These have suitable surface acidic characteristics and high specific surface area, which is conducive to the adsorption of alkanes and the desorption of alkenes and enhances Pt particle dispersion.…”
Section: Introductionmentioning
confidence: 99%